Perancangan Sistem Informasi Klinik Kecantikan Pada Rathu Beauty Care - Nada, Nadia Afsari; Afsari, Nadia; Rahmayani, Mentari Tri Indah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Beauty clinics compete to gain the trust of consumers by using the services of a beauty doctor. The current development of technology, the use of technology is one of the recommendations for how to help Rathu Beauty Care’s business processes. Through the use of current technology, applications can be built that in the future are expected to be able to help employees, doctors, and consumers at the Rathu Beauty Care clinic. The research method used by researchers to design this system is the SDLC Waterfall Method. In learning design, it is necessary to adjust the selection of design models to the system to be designed. This application helps consumers to order products online. This application helps employees to manage consumer data in terms of deleting, modifying and managing transaction reports. This application helps consumers and doctors in terms of question and answer online consultations.